Clinical value of ST-segment change after return of spontaneous cardiac arrest and emergent coronary angiography in patients with out-of-hospital cardiac arrest: Diagnostic and therapeutic importance of vasospastic angina. Issue 5 (August 2018) - Tateishi, Kazuya; Abe, Daisuke; Iwama, Tooru; Hamabe, Yuichi; Aonuma, Kazutaka; Sato, Akira
Background: We investigated the association between initial ST-segment change after return of spontaneous circulation (ROSC) and the incidence of acute coronary lesions in patients with out-of-hospital cardiac arrest (OHCA), and clinical outcomes of patients with OHCA caused by vasospastic angina pectoris (VSA). Methods: Among 2779 OHCA patients in our institution, all patients with ROSC underwent emergent coronary angiography (CAG) except for those with an obvious extra-cardiac cause of OHCA. Initial ST-segment changes after ROSC were reviewed, and 30-day survival and neurological outcome (Cerebral Performance Category) were evaluated. Results: Of the 155 patients, 52 (34%) had ST-segment elevation (STE) and 103 (66%) had non-STE. Significant coronary culprit lesions were present in 81% of patients with STE and in 33% of patients with non-STE ( P <.001). Percutaneous coronary intervention (PCI) was successful in 60 patients (93.8%) and failed in 4 patients (6.2%). Among 155 patients, 74 patients (47.7%) had favorable neurological prognosis, and 104 patients (67.1%) were alive at 30 days. ST-segment analysis showed good positive predictive value (81%) but low negative predictive value (68%) in diagnosing the presence of acute coronary lesions. VSA was found in 5 patients (9.6%) in the STE group and in 12 patients (11.7%) in the non-STE group. Of these 17 patients, 9 (52.9%) had favorable neurological outcome and 14 (82.4%) were alive at 30 days. Conclusion: An acute culprit lesion may be the cause of OHCA even in the absence of STE. In survivors of OHCA with normal coronary arteries, spasm provocation testing should be performed to detect VSA as a cause of the arrest.